Nutrition Information and Health Message on Sugar, Salt, and Fat Content on Ready-to-Serve Food Products in Indonesia: An Examination of Consumer and Producer Perspectives - Nasution, Zuraidah; Rimbawan, Rimbawan; Fajriaty, Deannisa; Nasir, Syifa Qolbiyah; Sutrisna, Aang; Sari, Eny Kurnia; Susanti, Eva (Journal of Consumer Sciences, 2024)
The popularity of ready-to-serve foods has increased in Indonesia, particularly among busy consumers with limited time for cooking at home. However, the consumption of ready-to-serve foods high in sugar, salt, and fat (SSF) has prompted concerns regarding their potential adverse health impacts when consumed excessively. The present study aimed to investigate consumers’ behavior and perception regarding the purchase of ready-to-serve foods and the practice of food producers in providing these products. The study employed a structured questionnaire involving 100 consumers selected based on purposive sampling. Additionally, focus group discussions were conducted with 80 ready-to-serve food producers across five Indonesian cities using a cross-sectional research design. The data analysis, conducted using binary logistics, yielded significant findings regarding the relationship between consumers’ income and their purchase decisions regarding ready-to-serve food. This study revealed that price (42%), taste (31%), and accessibility (23%) were the primary factors influencing consumers’ food choices. However, it also indicated that nutrition and health aspects received inadequate attention from consumers, which is a cause for concern. Concurrently, the producers who participated in this study indicated that they prioritize sanitation and hygiene (53.8%) in their food production, citing regulatory requirements as the primary driver of this practice. It is regrettable that the majority of the producers (92.5%) lacked information regarding the nutrition content of their products. Moreover, they did not actively contribute (2%-11%) to controlling SSF levels except to respond to consumers’ demands. These findings underscore the necessity for enhanced awareness campaigns and implementation strategies involving all stakeholders to promote healthier, ready-to-serve foods. The implications of these findings for future policy and practice are significant, highlighting the need for a more comprehensive approach to nutrition education and labeling in the ready-to-serve food industry in Indonesia.